In The Empire of Genghis Khan : a journey among nomads - Stewart, Stanley (Guilford, Connecticut : Lyons Press, 2002)
Describes the author's travels through Mongolia on horseback, including the terrain and scenery, people he meets, and daily encounters.
Includes Bibliographical References and Index.
Keywords: Asia Description and travel; Autobiography; Mongolia Description and travel